Policy challenges for the development of energy flexibility services. (February 2020) - Mlecnik, Erwin; Parker, James; Ma, Zheng; Corchero, Cristina; Knotzer, Armin; Pernetti, Roberta
Abstract: European energy policies call for an increased share of renewable energy sources and a more active role of the energy consumer. This is facilitated by, amongst others, buildings becoming energy flexible hubs, supporting smart energy grids with demand response strategies. While there is abundant technical research in this field, the related business and policy development is less well documented. This research scopes existing policy programmes and identifies opportunities and barriers to business development supporting energy flexible buildings. Using examples from seven European countries, this work reviews influencing niche management factors such as existing policy instruments, business development cases and identified stakeholder concerns, using literature research, narrative analysis and stakeholder research. National policy pathways show many differences but confirm that European buildings might become active players in the energy market, by providing energy storage, demand response and/or shifts in the use of energy sources. Slow sustained business development for energy flexibility services was mainly identified in the retail industry, and for energy service companies and aggregators. The direct involvement of end users in energy flexible buildings is still difficult. Stakeholders call for policy improvement, especially concerning the development of flexible energy tariffs, supporting incentives, awareness raising and more stakeholder-targeted business development. Highlights: Some existing policies allow buildings to be active players in the energy market. Policies to facilitate energy flexible buildings are not yet aligned within Europe. There are multiple barriers for stakeholders to engage in energy flexibility services. Future policy needs to focus on tariff development and supporting incentives. Stakeholder awareness should be raised and business developed around their needs.